LARVICULTURE OF SIAMESE FIGHTING FISH Betta splendens IN LOW-SALINITY WATER - Perez Fabregat, Thiago El Hadi; Wosniak, Barbara; Takata, Rodrigo; Miranda-Filho, Kleber Campos; Kochenborger Fernandes, Joao Batista [UNESP]; Portella, Maria Celia [UNESP] (Inst Pesca, 2017)
The low-salinity water may improve live food utilization during larviculture, mainly when larvae are fed with salt water organisms. This study aimed to determine the median lethal concentration (LC50) of NaCl in water for larvae of Betta splendens, an important ornamental species, and to evaluate the effect of low-salinity on the larviculture during the first 15 days of exogenous feeding. In the first experiment, 400 larvae were stocked in forty 250 mL aquariums, and exposed to ten saline concentrations. In the second experiment, 360 larvae were distributed in 24 1 L aquariums, in a factorial design 2x3 comprising two increasing prey densities, starting with 50 and 100 Artemia nauplii larva(-1), and three concentrations of NaCl (0, 2 and 4 g NaCl L-1). After 24, 48, 72 and 96 h of exposure, the LC50 were 11.7, 10.1, 8.2 and 7.1 g NaCl L-1, respectively. At the end of the experiment 2, larvae reared in salinity of 2 and 4 g NaCl L-1 and fed with the initial prey density of 100 nauplii larvae(-1) were bigger and heavier. The use of low-saline water (2 to 4 g NaCl L-1) is a safe protocol for larviculture of Siamese fighting fish as it does not affect the survival and optimizes the use of Artemia nauplii when higher prey densities are used.
Keywords: Intensive larviculture; toxicity; live food; salinity; ornamental fish